Family at Watkins' Home - Watkins, Howard::::::::: (1980)
Linda Gomez holding David Gomez, Doreen Gomez, Diane Gomez, Christine Watkins, Albert Watkins holding Adam Watkins; Back: Dawn Gomez, Rose Watkins On front porch; Adam and Albert looking at each other